In Situ Subtalar Arthrodesis for Posttraumatic Arthritis of the Calcaneus. (August 2016) - Probe, Robert
Abstract : Summary: One of the most frequent complications after intraarticular fracture of the calcaneus is the development of posttraumatic arthritis of the subtalar joint. If conservative measures fail in the treatment of this condition, consideration of arthrodesis should be given. This video depicts the preoperative assessment and surgical technique applied to one such 54-year-old patient who had undergone internal fixation of a calcaneal fracture 9 years before. Shown within the video is exposure of the subtalar joint through a lateral incision, joint preparation, and the application of stable fixation. Subtleties of exposure, osteogenesis maximization, and postoperative management are covered.